Biomimicking Nano‐Micro Binary Polymer Brushes for Smart Cell Orientation and Adhesion Control. Issue 25 (17th May 2016) - Chen, Lina; Xie, Zhuang; Gan, Tiansheng; Wang, Yi; Zhang, Guangzhao; Mirkin, Chad A.; Zheng, Zijian
Abstract : A new biomimetic surface named nano‐micro binary polymer brushes is fabricated by large‐area bench‐top dip‐pen nanodisplacement lithography technique. It is composed of gelatin‐modified poly(glycidyl methacrylate) nanolines which are spaced by microstripes of poly( N ‐isopropylacrylamide). Cells are not only adhered and oriented well on the re‐used surface, but also detachable from the surface with well‐preserved extracellular matrix and aligned morphology.